Divalent cations and the divergence of βγ-crystallin function. - Roskamp, Kyle (Biochemistry, 2019)
The βγ-crystallin superfamily contains both the β- and γ-crystallins of the vertebrate eye lens and the microbial calcium-binding proteins, all of which are characterized by a common double-Greek key domain structure. The vertebrate βγ-crystallins are long-lived structural proteins that refract light onto the retina. In contrast, the microbial βγ-crystallins bind calcium ions. The βγ-crystallin from the tunicate Ciona intestinalis (Ci-βγ) provides a potential link between these two functions: it binds calcium with high affinity and is found in a light-sensitive sensory organ that is highly enriched in metal ions. Thus Ci-βγ is valuable for investigating the evolution of the βγ-crystallin fold away from calcium binding and toward stability in the apo form as part of the vertebrate lens. Here we investigate the effect of Ca(2+) and other divalent cations on the stability and aggregation propensity of Ci-βγ and human γS-crystallin (H S). Beyond Ca(2+), Ci-βγ is capable of coordinating Mg(2+), Sr(2+), Co(2+), Mn(2+), Ni(2+), and Zn(2+), although only Sr(2+) is bound with comparable affinity to its preferred metalion. The extent to which the tested divalent cations stabilize Ci-βγ structure correlates strongly with ionic radius. In contrast, none of the tested divalent cations improved the stability of HγS, and some of them induced aggregation. Zn(2+), Ni(2+), and Co(2+) induce aggregation by interacting with cysteine residues, whereas Cu(2+)-mediated aggregation proceeds via a different binding site.